2020
DOI: 10.4081/monaldi.2020.1207
|View full text |Cite
|
Sign up to set email alerts
|

Convex probe endobronchial ultrasound guided transbronchial/transoesophageal fine needle aspiration (C-EBUS-TBNA/EUS-B FNA) of pleural lesions: A single center experience and review of literature

Abstract: The evaluation of pleural diseases has been well established. If pleurocentensis is non-diagnostic, the second investigation depending upon availability could be either closed pleural biopsy or image guided pleural biopsy or thoracoscopic pleural biopsy (medical or surgical). Pleural disease presenting as thickness/mass/nodule in the mediastinum is difficult to access through ultrasound or computed tomography and will need thoracoscopy. Thoracoscopy is an invasive procedure which can be difficult to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similarly, EBUS-TBNA and EUS-B-FNA could be both used to diagnose metastatic involvement of the pleura, as reported in various case series [85,88,89] by renal cell carcinoma, adenoid cystic adenocarcinoma and Hodgkin's B cell lymphoma.…”
Section: Pleural and Cardiac Lesionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly, EBUS-TBNA and EUS-B-FNA could be both used to diagnose metastatic involvement of the pleura, as reported in various case series [85,88,89] by renal cell carcinoma, adenoid cystic adenocarcinoma and Hodgkin's B cell lymphoma.…”
Section: Pleural and Cardiac Lesionsmentioning
confidence: 87%
“…The approach to pleural lesions suspected for mesothelioma could also be performed by the esophagus with the EUS-B-FNA technique, as it was reported in four case reports [87][88][89][90], where the pleural thickness was in close proximity to the esophagus with a high diagnostic yield.…”
Section: Pleural and Cardiac Lesionsmentioning
confidence: 99%
“…In several of these patients, echo‐endoscopy was not the only procedure that was undertaken. While EBUS‐TBNA was performed in nine of these cases, 11–16 in the other four patients EUS‐B FNA was performed: two patients had mesothelioma, one had lymphoma and one had metastatic renal carcinoma 16,17 . It has previously been reported that a 22‐gauge needle was used in eight patients 11,13,14,16 and 21‐gauge in one patient 17 …”
Section: Discussionmentioning
confidence: 99%